Risk Factors for Community-Associated Clostridium difficile Infection in Children. (4th October 2017) - Weng, Mark; Adkins, Susan H; Farley, Monica; Espinosa, Catherine C; Reisenauer, Claire; Whitten, Tory; Hancock, Emily B; Dumyati, Ghinwa; Davis, Corinne M; Wilson, Lucy; Beldavs, Zintars G; Mcdonald, L Clifford; et al.
Abstract: Background: Incidence of Clostridium difficile infection (CDI) in children has been shown to be highest among those aged 1 to 3 years, with similar clinical presentation, disease severity, and outcomes as older children. In addition, a large proportion of CDI in children are community-associated (CA), but few data exist regarding associated risk factors. We sought to identify CA-CDI risk factors in younger children. Methods: We enrolled children from 8 geographically-diverse U.S. sites during October 2014–February 2016. Case-patients were defined as children aged 12–60 months with a positive C. difficile stool specimen collected as an outpatient or within 3 days of hospitalization, who had no healthcare facility admission in the prior 12 weeks and no history of CDI. Each case-patient was matched to one randomly selected control (child with no prior history of CDI) by site and age group. Caretakers were interviewed about participants' relevant exposures in the 12 weeks prior to case-patient's illness onset date; univariate analysis was performed using exact conditional logistic regression. Results: Of 138 children, 43.5% were female; 69.6% were 12–23 months old. A significantly higher proportion of cases than controls had: an underlying chronic medical condition (33.3% vs 11.9%; P = 0.02); a neonatal intensive care unit (NICU) stay at time of birth (26.9% vs 13.2%; P = 0.04); or recent antibiotic exposure (53.6% vs 20.6%; P = 0.0001). More cases than controls had recent higher-risk outpatient healthcare exposures (emergency department, outpatient procedure and surgical centers, hospital-based outpatient settings, or urgent care) (34.9% vs 19.1%; P = 0.06) or a household member with diarrhea (36.2% vs 20.6%; P = 0.05). No difference was found in the proportion of cases and controls who had a feeding tube (2.9% vs 0%; P = 0.50) or a recent exposure to gastric acid suppressants (6.1% vs 2.9%; P = 0.63). Conclusion: Young children with underlying disease, NICU stay, or recent antibiotic use might be at higher risk for CA-CDI. Improving outpatient antibiotic use, particularly among children with comorbidities, might reduce CA-CDI in this population. Further investigation of other risk factors, including outpatient healthcare and household exposures, is needed. Disclosures: All authors: No reported disclosures.